First survey on association of TMEM154 and CCR5 variants with serological maedi-visna status of sheep in German flocks - Molaee, Vahid; Eltanany, Marwa; Lühken, Gesine; Justus Liebig University Giessen (My University, 2018)
Maedi-visna, a disease caused by small ruminant lentiviruses (SRLVs), is present in sheep from many countries, also including Germany. An amino acid substitution (E/K) at position 35 of the transmembrane protein 154 (TMEM154) as well as a deletion in the chemokine (C-C motif) receptor type 5 gene (CCR5) were reported to be associated with the serological MV status and/or the SRLV provirus concentration in North American sheep populations. The aim of this study was to test if those two gene variants might be useful markers for MV susceptibility in Germany. For this purpose, more than 500 sheep from 17 serologically MV positive German sheep flocks with different breed backgrounds were genotyped applying PCR-based methods. Both, crosstab and non-parametric analyses showed significant associations of the amino acid substitution at position 35 of TMEM154 with the serological MV status (cut-off-based classification) and the median MV ELISA S/P value in all samples and in two of the four analyzed breed subsets. The deletion in the CCR5 promoter did not show a consistent association with serological MV status or median ELISA S/P value. It can be concluded that the amino acid substitution at position 35 of TMEM154 is a promising marker for breeding towards a lower number of serologically MV positive sheep in German flocks, at least in flocks of the Texel breed, while this remains questionable for the deletion in the CCR5 promoter. The findings of this study still need to be verified in additional sheep breeds.
Keywords: ddc:630